2013
DOI: 10.1007/s00134-013-3056-z
|View full text |Cite
|
Sign up to set email alerts
|

Hospital mortality prognostication in sepsis using the new biomarkers suPAR and proADM in a single determination on ICU admission

Abstract: SuPAR and, to a lesser extent, proADM levels on ICU admission were better tools in prognosticating in-hospital mortality than CRP or PCT. However, neither of the two new biomarkers has been demonstrated to be excessively useful in the current setting. The prognostic accuracy was better for severity scores than for any of the biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 36 publications
10
62
1
3
Order By: Relevance
“…The ROC-AUC for mortality of suPAR was comparable to previous investigations in ventilated critically ill patients, which could have included many patients with ARDS [6][7][8]. However, the ROC-AUC was low, which could at least in part be because of the high mortality in these patients.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The ROC-AUC for mortality of suPAR was comparable to previous investigations in ventilated critically ill patients, which could have included many patients with ARDS [6][7][8]. However, the ROC-AUC was low, which could at least in part be because of the high mortality in these patients.…”
Section: Discussionsupporting
confidence: 74%
“…suPAR is an emerging biomarker in sepsis research. Previous studies in critically ill patients with sepsis or bacteremia have shown a strong association between increasing levels of plasma suPAR and mortality [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…In addition to its associations to atherosclerosis, suPAR has also been shown to be a good prognostic marker of in-hospital mortality in patients suffering severe infection and septic shock (35), as well as being a prognostic marker in cardiovascular mortality in a black South African population (36) and various other settings (24,36). Interestingly, in a study of 60 patients undergoing coronary artery bypass surgery, perioperative levels of suPAR remained stable despite the extensive inflammatory reaction induced by such major surgery (37).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ADM may become a suitable marker for prognostic estimations in sepsis patients in the future. Furthermore, in one clinical investigation, ADM had a significantly higher prognostic significance for in-hospital mortality than the classical markers CRP and PCT [70].…”
Section: Proadrenomedullin and Soluble Subtype Of The Cd14 Cell Surfamentioning
confidence: 92%
“…In clinical studies, proADM was of higher prognostic value for sepsis patients with nosocomial pneumonia (hospital-acquired pneumonia, HAP) than the classical biomarkers CRP and PCT [69,70]. However, since raised plasma levels of ADM are seen in diverse diseases, e. g., cardiovascular and autoimmune diseases [71], ADM is unsuitable for initial detection of sepsis.…”
Section: Proadrenomedullin and Soluble Subtype Of The Cd14 Cell Surfamentioning
confidence: 99%